The Development Of Halal Literacy In Indonesia From Tradition To Modernity - Haryanti, Peni; Khusnudin, Khusnudin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study explores the historical development of halal literacy in Indonesia, from traditional oral transmission by religious leaders to a modern, structured system. Halal knowledge was shared informally through religious teachings and local customs in the early stages. However, globalization and the rise of the halal economy have transformed halal literacy into a formal system. This shift is marked by establishing the Badan Penyelenggara Jaminan Produk Halal (BPJPH) and integrating digital technology into the halal certification process. The study highlights key challenges in promoting halal literacy, such as limited public awareness of halal products beyond food and restricted access to halal certification for small and medium enterprises (SMEs). Despite these challenges, Indonesia has significant potential to become a global leader in the halal market through technological innovation, enhanced education, and government support. This research aims to provide a deeper understanding of the importance of halal literacy in the daily lives of Indonesian Muslims and its role in the future development of the halal industry.